Preparation method of high-entropy metal ceramic material and high-entropy metal ceramic material
By preparing a composite powder of CuzFeNiCryX high-entropy alloy and MC carbide, using powder thermoforming technology to replace the Co-bonded phase, the problem of bonding phase excitation isotopes of WC-based ceramic materials in radiation environment is solved, and high-entropy metal cermet is achieved The material's high corrosion resistance and radiation damage resistance extend the service life of the reactor and expand the scope of application.
Patent Information
- Application Number
- CN202411795403.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The existing WC-based ceramic materials bind phase-exciting isotopes in a long-term radiation environment, resulting in an extended nuclear radiation half-life, increasing maintenance time and nuclear fuel shielding costs, and limiting their promotion and application in the field of nuclear power.
CuzFeNiCryX high-entropy alloy powder is used for ball milling and mixing with MC carbides, and high-entropy metal cermet materials are prepared through powder thermoforming technology to replace the traditional Co-bonded phase, and improve the material's radiation damage resistance and corrosion resistance.
It significantly improves the corrosion resistance and radiation damage resistance of high-entropy metal cermet materials, extends the service life of the reactor, and expands its application range.
Smart Images

Figure CN119287200A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present disclosure relate to the technical field of ceramic powders, and in particular to a preparation method of a high-entropy metal ceramic material and a high-entropy metal ceramic material. Background Art
[0002] At present, lead-based reactors using liquid lead or lead-bismuth alloy as coolant have significant advantages in safety, economy, miniaturization and sustainability. Dynamic / static load-bearing components such as supports and guide cylinders play a key role in maintaining the stable operation of the reactor, but they are prone to corrosion failure during service, which seriously affects the stability of reactor operation.
[0003] To solve the above problems, developing structural materials with excellent corrosion resistance is one of the effective solutions. In the related technology, WC-based cermets have excellent hardness, corrosion resistance and wear resistance, but in a long-term radiation environment, the Co bonding phase of WC-based cermets will gradually excite to form Co-60 isotopes, prolonging the half-life of nuclear radiation, resulting in increased maintenance time and nuclear fuel shielding costs, which greatly limits its promotion and application in the field of nuclear power. Summary of the invention
[0004] The purpose of the present disclosure is to provide a preparation method of a high entropy metal ceramic material and a high entropy metal ceramic material, thereby overcoming the problem of poor performance of high entropy metal ceramic materials caused by the limitations and defects of related technologies at least to a certain extent.
[0005] According to one aspect of the present disclosure, a method for preparing a high entropy metal ceramic material is provided, comprising: Preparation of Cu z FeNiCr y X high entropy alloy powder, based on Cu z FeNiCr y X high entropy alloy powder and MC carbide are used to prepare metal-ceramic composite powder, and the metal-ceramic composite powder is ball-milled to obtain MC-Cu with dispersed carbide particles. z FeNiCr y X metal ceramic powder; MC-Cu is formed by powder hot forming technology z FeNiCr y X metal ceramic powder is prepared into a metal ceramic block to obtain a high entropy metal ceramic material.
[0006] In an exemplary embodiment of the present disclosure, the Cu z FeNiCr y X high entropy alloy powder is prepared by vacuum atomization method and is used to prepare Cu z FeNiCry The process parameters of X high entropy alloy powder include: air pressure 1~10 MPa, air flow velocity 100~200 mm / s, and air flow injection angle 30~90°.
[0007] In an exemplary embodiment of the present disclosure, the Cu z FeNiCr y X in the X high entropy alloy powder includes any one of Co, Al and Ti; Cu z FeNiCr y The range of z and y in X high entropy alloy powder is 0~1.0 at%, Cu z FeNiCr y The particle size of X high entropy alloy powder is 0.1~15 μm.
[0008] In an exemplary embodiment of the present disclosure, the MC carbide is WC, WC-Cr3C2 or WC-B4C, and the particle size of the MC carbide is 1-3 μm.
[0009] In an exemplary embodiment of the present disclosure, the MC-Cu z FeNiCr y X metal ceramic powder contains 5~40wt% Cu z FeNiCr y X high entropy alloy powder and 60~95 wt% MC carbide.
[0010] In an exemplary embodiment of the present disclosure, 0.1-1.0 wt % of a grain inhibitor and 0.1-1.0 wt % of an antioxidant are added during the ball milling mixing process, and the grain inhibitor includes chromium carbide and vanadium carbide.
[0011] In an exemplary embodiment of the present disclosure, the ball milling time is 20 to 40 h, the ball milling rotation mode is in a cyclic forward-reverse alternation, the ball milling speed is 100 to 300 r / min, and the MC-Cu obtained after ball milling is z FeNiCr y The particle size of X metal ceramic powder is 0.5~5 μm.
[0012] In an exemplary embodiment of the present disclosure, the MC-Cu z FeNiCr y X metal ceramic powder is prepared into a metal ceramic block, including: MC-Cu z FeNiCr y X metal ceramic powder is dried and kept warm, and MC-Cu is formed by powder hot forming technology. zFeNiCr y The X metal ceramic powder is sintered to prepare the high entropy metal ceramic material.
[0013] In an exemplary embodiment of the present disclosure, the sintering pressure is 10-40 MPa, the sintering temperature is 900-1400° C., and the insulation time is 5-120 min.
[0014] According to one aspect of the present disclosure, a high entropy metal ceramic material is provided, wherein the high entropy metal ceramic material is prepared according to any one of the above-mentioned methods for preparing a high entropy metal ceramic material.
[0015] In the technical solution provided in the embodiments of the present disclosure, on the one hand, high entropy alloy powder is prepared based on the unique characteristics of high entropy alloy such as resistance to radiation damage, high oxidation resistance and good wettability. The use of high entropy alloy as the metal phase can reduce the proportion of active element components inside the coating and greatly improve the material's resistance to radiation damage. Taking into full consideration the characteristics of high wettability, high toughness, corrosion resistance and radiation damage resistance of the bonding phase of the composite material, four elements with similar atomic radius, Fe, Ni, Cr and Cu, are selected as the basic elements of the high entropy alloy powder to form a high entropy alloy with FCC structure. Among them, the three elements of Fe, Ni and Cr can increase the chaos entropy of the alloy and promote the formation of high entropy alloys; the addition of Cr element is also beneficial to the formation of Cr2O3, which improves the corrosion resistance of the alloy; the addition of Cu element improves the wettability of the high entropy alloy and the carbide hard phase, and improves the density and cohesive strength of the composite material; the doping of elements such as Co, Al and Ti can adjust the degree of lattice distortion of the FCC phase of the high entropy alloy, change the mechanical properties of the alloy, and realize the functional diversification of the composite material. On the other hand, the use of Cu z FeNiCr y X high entropy alloy powder replaces the Co binding phase. Compared with traditional metal ceramics, the metal phase is high-entropy to obtain a high-entropy metal-ceramic composite material with high strength and toughness and excellent resistance to radiation damage. The prepared high-entropy metal-ceramic material has better corrosion resistance, which can significantly improve the service life and stability of the reactor and increase the scope of application. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings herein are incorporated into the specification and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the specification are used to explain the principles of the present disclosure. Obviously, the accompanying drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without creative work.
[0017] Figure 1 A flow chart schematically illustrates a method for preparing a high entropy metal ceramic material in an embodiment of the present disclosure.
[0018] Figure 2 The schematic diagram of the process of preparing the metal ceramic block is shown schematically.
[0019] Figure 3 This is a surface morphology of the high entropy alloy powder prepared in Example 1 of the present disclosure.
[0020] Figure 4 This is a cross-sectional morphology diagram of a high entropy metal ceramic block prepared according to Example 1 in the embodiments of the present disclosure.
[0021] Figure 5 These are the test results of the friction and wear rate of the high entropy metal ceramic blocks prepared according to Examples 1 to 3.
[0022] Figure 6 These are the neutral salt spray corrosion performance test results of the metal ceramic blocks prepared according to Example 3 and Example 4 in the embodiments of the present disclosure.
[0023] Figure 7 The hardness and bending strength test results of the metal ceramic blocks prepared according to Example 3 and the comparative example. DETAILED DESCRIPTION
[0024] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as being limited to the examples set forth herein; on the contrary, these embodiments are provided so that the present disclosure will be more comprehensive and complete, and the concepts of the example embodiments are fully conveyed to those skilled in the art. The described features, structures, or characteristics may be combined in one or more embodiments in any suitable manner. In the following description, many specific details are provided to provide a full understanding of the embodiments of the present disclosure. However, those skilled in the art will appreciate that the technical solutions of the present disclosure may be practiced while omitting one or more of the specific details, or other methods, components, devices, steps, etc. may be adopted. In other cases, known technical solutions are not shown or described in detail to avoid obscuring various aspects of the present disclosure.
[0025] The terms "a", "an", "the" and "said" used in this specification are used to indicate the presence of one or more elements / components, etc.; the terms "including" and "having" are used to express an open-ended inclusion and mean that there may be additional elements / components, etc. in addition to the listed elements / components, etc.; the terms "first" and "second" etc. are used only as labels and are not intended to limit the quantity of their objects.
[0026] In order to solve the above technical problems, the present disclosure provides a method for preparing a high entropy metal ceramic material, which is used to prepare a high entropy metal ceramic material. Figure 1As shown in , it mainly includes the following steps: In step S110, Cu z FeNiCr y X high entropy alloy powder and MC carbide are ball-milled to obtain MC-Cu with dispersed carbide particles. z FeNiCr y X metal ceramic powder; In step S120, MC-Cu is formed by powder hot forming technology. z FeNiCr y X metal ceramic powder is prepared into a metal ceramic block to obtain a high entropy metal ceramic material.
[0027] Next, the preparation method of the high entropy metal ceramic material in the embodiment of the present disclosure is specifically described.
[0028] In step S110, Cu z FeNiCr y X high entropy alloy powder and MC carbide are ball-milled to obtain MC-Cu with dispersed carbide particles. z FeNiCr y X Metal ceramic powder.
[0029] In the disclosed embodiment, Cu z FeNiCr y X high entropy alloy powder is a powder prepared by vacuum atomization. z FeNiCr y The process of preparing CuX high entropy alloy powder z FeNiCr y The process parameters of X high entropy alloy powder include: gas pressure of 1~10 MPa, gas flow velocity of 100~200 mm / s, and gas flow injection angle of 30~90°.
[0030] In some embodiments, the high entropy alloy is a new type of multi-principal alloy material, which has high strength, high hardness, excellent corrosion resistance, high temperature softening resistance and unique radiation resistance. z FeNiCr y The element X in the X high entropy alloy powder includes any one of Co, Al and Ti, which is determined according to actual needs. z FeNiCr y The range of z in X high entropy alloy powder is 0~1.0 at%, Cu z FeNiCr y The range of y in X high entropy alloy powder is 0~1.0 at%, Cu z FeNiCry The particle size of X high entropy alloy powder is 0.1~15μm. High entropy alloy has the characteristics of radiation damage resistance, high oxidation resistance and good wettability. Based on this, using high entropy alloy powder as the metal phase can reduce the proportion of active elements in the coating and greatly improve the material's resistance to radiation damage.
[0031] In the embodiments of the present disclosure, MC-Cu is prepared based on the unique radiation damage resistance, high oxidation resistance and good wettability of high entropy alloys. z FeNiCr y X new metal-ceramic composite powder. The use of high entropy alloy as the metal phase can reduce the proportion of active element components inside the coating and greatly improve the material's resistance to radiation damage. Furthermore, the disclosed embodiment fully considers the characteristics of high wettability, high toughness, corrosion resistance and radiation damage resistance of the composite material bonding phase, and selects Fe, Ni, Cr and Cu, four elements with similar atomic radius, as the basic elements of high entropy alloy powder to form a high entropy alloy with FCC structure. Among them, the three elements of Fe, Ni and Cr can increase the chaotic entropy of the alloy and promote the formation of high entropy alloys; the addition of Cr elements is also conducive to the formation of Cr2O3, which improves the corrosion resistance of the alloy; the addition of Cu elements can increase the wettability of high entropy alloys and carbide hard phases, and improve the density and cohesive strength of the composite material; the doping of elements such as Co, Al and Ti can adjust the degree of lattice distortion of the FCC phase of the high entropy alloy, change the mechanical properties of the alloy, and realize the functional diversification of the composite material.
[0032] Among them, MC carbide includes any one of WC, WC-Cr3C2 and WC-B4C, which is determined according to actual needs. The particle size of MC carbide is 1~3 μm.
[0033] In some embodiments, Cu z FeNiCr y The weight percentage of the X high entropy alloy powder is 5-40 wt%, and the weight percentage of the MC carbide is 60-95 wt%.
[0034] After obtaining Cu z FeNiCr y After X high entropy alloy powder and MC carbide, Cu z FeNiCr y X high entropy alloy powder and MC carbide are ball-milled to prepare MC-Cu z FeNiCr y X Metal Ceramic Powder, MC-Cu z FeNiCr y X metal ceramic powder can be MC-Cu with dispersed carbide particles. z FeNiCr yX metal ceramic powder. MC-Cu z FeNiCr y X metal ceramic powder mainly contains 5~40 wt% Cu z FeNiCr y X high entropy alloy powder and 60~95 wt% MC carbide. z FeNiCr y X high entropy alloy powder is used as the metal phase.
[0035] During the ball milling process, 0.1-1.0 wt% of a grain inhibitor and 0.1-1.0 wt% of an antioxidant may also be added. The grain inhibitor is used to inhibit grain growth during sintering, and the antioxidant is used to inhibit oxidation during sintering. Excessively large grains and oxidation will weaken the hardness, fracture toughness and wear resistance of the material. The grain inhibitor may include two complex phase carbides. The two complex phase carbides may include chromium carbide and vanadium carbide, wherein the ratio of chromium carbide to vanadium carbide may be any suitable ratio, as long as the weight percentage of chromium carbide to vanadium carbide is 0.1-1.0 wt%. The antioxidant may be carbohydrazide. It should be noted that when adding a grain inhibitor and an antioxidant during the ball milling process, the amount of the grain inhibitor and the antioxidant added may be the same.
[0036] Furthermore, the metal-ceramic composite powder can be weighed and proportioned, and the metal-ceramic composite powder includes Cu z FeNiCr y X high entropy alloy powder and MC carbide, in addition, may also contain grain inhibitors and antioxidants. Of course, the metal-ceramic composite powder may also contain only Cu z FeNiCr y X high entropy alloy powder and MC carbide, without grain inhibitor and antioxidant. Based on this, the prepared metal ceramic composite powder and deionized water can be ball milled and mixed according to a preset ratio, and the preset ratio can be 1:2 or other suitable ratios, which are determined according to actual needs.
[0037] During the ball milling process, the ball milling method can be wet milling. For example, the ball milling time can be 20 to 40 hours, and the rotation method during the ball milling process is to rotate in a forward-reverse alternating manner in a cycle, and 2 to 5 hours can be used as a cycle for forward-reverse alternating rotation. The rotation speed during the ball milling process is 100 to 300 r / min, and the MC-Cu obtained after ball milling z FeNiCr y The particle size of X metal ceramic powder is 0.5~5 μm.
[0038] The disclosed embodiment adopts measures such as long aging, positive-reverse alternation and wet ball milling to achieve uniform distribution of WC particles and high entropy alloy phases, which not only effectively solves the problem of WC particle segregation in the process of mixing WC-based powder by traditional ball milling, but also avoids the problem of sticking of high entropy alloy phases at high temperatures, ensuring the stability of the content of each phase in the composite powder. Furthermore, the disclosed embodiment adopts a grain inhibitor to inhibit the growth of carbide grains during high-temperature sintering, which can simultaneously inhibit the excessive growth of nano-scale and submicron-scale carbide particles during the sintering process, and effectively improve the mechanical properties of the composite material. The disclosed embodiment adds an antioxidant to the composite powder to eliminate oxide impurities generated during the ball milling of the composite powder, which not only helps to improve the density of the sintered block, but also can inhibit crack initiation and expansion behavior under high external stress, and improve the overall fracture toughness of the material. In addition, by inhibiting crack expansion behavior, the number of corrosion channels can be reduced, further improving the corrosion resistance of the material.
[0039] Next, in step S120, MC-Cu is formed by powder hot forming technology. z FeNiCr y X metal ceramic powder is prepared into a metal ceramic block to obtain a high entropy metal ceramic material.
[0040] In the embodiment of the present disclosure, the powder hot forming technology includes any one of hot pressing sintering, hot isostatic pressing and spark plasma sintering. z FeNiCr y X metal ceramic powder is dried and kept warm, and MC-Cu is formed by powder hot forming technology. z FeNiCr y X metal ceramic powder is sintered to prepare high entropy metal ceramic material. z FeNiCr y The X metal ceramic powder is placed in a blast drying oven for heat preservation. The drying temperature can be 80°C to 90°C and the heat preservation time can be 10 to 12 hours.
[0041] Furthermore, the MC-Cu after heat preservation can be z FeNiCr y The X metal ceramic powder is sieved, and the sieve used for sieving can be 200 mesh, 300 mesh, etc., which is determined according to actual needs, as long as the powder particles can be small and evenly dispersed.
[0042] On this basis, MC-Cu can be formed by powder hot forming technology. z FeNiCr yX metal ceramic powder is prepared into a metal ceramic block. In some embodiments, MC-Cu z FeNiCr y The X metal ceramic powder is sintered to prepare a metal ceramic block, so that the metal ceramic block is used as a high entropy metal ceramic material.
[0043] During the sintering process, the sintering pressure is 10~40 MPa, the sintering temperature is 900~1400℃, and the holding time is 5~120 min.
[0044] Based on this, reference Figure 2 As shown in the figure, the process of preparing the metal ceramic block in the embodiment of the present disclosure may mainly include the following steps: First, the single metal is smelted by vacuum atomization to obtain high entropy alloy powder. The high entropy alloy powder and MC carbide are mixed to obtain a batch, and a grain inhibitor and an antioxidant are added to the batch to obtain a metal-ceramic composite powder, which is then ball-milled, dried and sieved, and then sintered to obtain MC-Cu z FeNiCr y X metal ceramic block, so as to use it as a high entropy metal ceramic material.
[0045] In the embodiments of the present disclosure, high performance MC-Cu is achieved by using powder hot forming technologies such as hot pressing sintering, hot isostatic pressing and spark plasma sintering. z FeNiCr y Stable preparation of X metal ceramic blocks. The appropriate sintering pressure and temperature ratio can avoid the overflow and loss of liquid high entropy alloy along the gap between the hot pressing mold and the sample, effectively ensuring the stability of the sample structure and performance. Under the process parameters of the present disclosure, the high entropy alloy binder phase can be fully melted into a liquid phase to coat WC particles of different particle sizes and tightly bond each hard particle, effectively improving the density and mechanical properties of the composite material. In addition, the embodiment of the present disclosure combines the high corrosion resistance of carbides and the high resistance to radiation damage of high entropy alloys, supported by powder mixing technology and hot pressing molding technology with the characteristics of long aging, positive-reverse alternation and wet ball milling, using Cu z FeNiCr y X high entropy alloy replaces the Co bonding phase. Compared with traditional metal ceramics, high entropy metal ceramics have better corrosion resistance and can significantly improve the service life and stability of the reactor.
[0046] Next, the preparation method of the high entropy metal ceramic material provided by the present disclosure is described in detail with reference to the examples.
[0047] Example 1 In this embodiment, a WC-10wt%CuFeNiCrCo metal ceramic block is prepared, and the specific implementation steps are as follows: Step 1: Prepare CuFeNiCrCo high entropy alloy powder using vacuum air atomization powder making equipment. The process parameters of vacuum air atomization include: air pressure of 3 Mpa, air flow velocity of 150 mm / s, and air flow injection angle controlled at 45°. The particle size of the prepared CuFeNiCrCo high entropy alloy powder is 0.1-15 μm.
[0048] Step 2: weigh and proportion the metal-ceramic composite powder, which may be, for example, a WC-CuFeNiCrCo composite powder. When a grain inhibitor and an antioxidant are added, the metal-ceramic composite powder includes 10 wt% of CuFeNiCrCo high entropy alloy powder, 90 wt% of WC powder, 0.4 wt% of a grain inhibitor (complex phase carbide) and 0.4 wt% of an antioxidant.
[0049] Step 3: The WC-CuFeNiCrCo composite powder and deionized water are ball-milled in a ratio of 1:2 for 30 h. The rotation mode of the ball mill is alternating forward and reverse rotation (one cycle of 5 h) at a speed of 200 r / min. The particle size of the composite powder after ball milling is 0.5~5 μm.
[0050] Step 4: Place the ball-milled composite powder in a forced air drying oven at 80° C. for 10 h. After drying, sieve the composite powder using a 200-mesh sieve to ensure that the powder particles are fine and evenly dispersed.
[0051] Step 5: Prepare the WC-CuFeNiCrCo metal ceramic block by spark plasma sintering technology, wherein the sintering pressure is 30 MPa, the sintering temperature is 1300° C., and the holding time is 5 min.
[0052] Figure 3 The morphology of the prepared CuFeNiCrCo high entropy alloy powder is shown in Figure 1. As can be seen from the figure, the prepared CuFeNiCrCo high entropy alloy powder is spherical, the powder surface is dense and smooth, and there are no defects such as holes, indicating that the powder preparation effect is excellent; the overall powder particle size is less than 15 μm, which meets the subsequent processing requirements.
[0053] Figure 4 This is a cross-sectional SEM image of a WC-CuFeNiCrCo metal ceramic block prepared according to Example 1. As can be seen from the figure, most of the WC and the CuFeNiCrCo high entropy alloy are tightly bonded, and the overall structure inside the material is dense without obvious defects such as large-sized holes and cracks.
[0054] Example 2 In this embodiment, a WC-10wt%CuFeNiCrCo metal ceramic block is prepared, and the specific implementation steps are as follows: Step 1: Prepare CuFeNiCrCo high entropy alloy powder using vacuum air atomization powder making equipment. The process parameters of vacuum air atomization include: air pressure of 5 MPa, air flow velocity of 100 mm / s, and air flow injection angle controlled at 45°. The particle size of the prepared CuFeNiCrCo high entropy alloy powder is 0.1~15 μm.
[0055] Step 2: weigh and mix the metal-ceramic composite powder. The metal-ceramic composite powder can be, for example, a WC-CuFeNiCrCo composite powder. When a grain inhibitor and an antioxidant are added, the metal-ceramic composite powder includes 10 wt% of CuFeNiCrCo high entropy alloy powder, 90 wt% of WC powder, 0.8 wt% of a grain inhibitor (complex phase carbide) and 0.8 wt% of an antioxidant.
[0056] Step 3: The metal-ceramic composite powder and deionized water are ball-milled in a ratio of 1:2 for 40 h. The rotation mode of the ball mill is alternating forward and reverse (one cycle of 5 h) at a speed of 300 r / min. The particle size of the composite powder after ball milling is 0.5~5 μm.
[0057] Step 4: The ball-milled composite powder is kept at 80° C. in a forced air drying oven for 5 h, and then sieved with a 400-mesh sieve to ensure that the powder particles are fine and evenly dispersed.
[0058] Step 5: Prepare the WC-CuFeNiCrCo metal ceramic block by spark plasma sintering technology, wherein the sintering pressure is 20 MPa, the sintering temperature is 900 °C, and the holding time is 10 min.
[0059] Example 3 This example is used to prepare a WC-10wt%CuFeNiCrCo metal ceramic block, and the specific implementation steps are as follows: Step 1: Prepare CuFeNiCrCo high entropy alloy powder using vacuum air atomization powder making equipment. The process parameters of vacuum air atomization include: air pressure of 10 MPa, air flow velocity of 200 mm / s, and air flow injection angle controlled at 45°. The particle size of the prepared CuFeNiCrCo high entropy alloy powder is 0.1~15 μm.
[0060] Step 2: weigh and mix the metal-ceramic composite powder. The metal-ceramic composite powder can be, for example, a WC-CuFeNiCrCo composite powder. When a grain inhibitor and an antioxidant are added, the metal-ceramic composite powder includes 10 wt% of CuFeNiCrCo high entropy alloy powder, 90 wt% of WC powder, 0.2 wt% of a grain inhibitor (complex phase carbide) and 0.2 wt% of an antioxidant.
[0061] Step 3: The composite powder and deionized water are ball-milled in a ratio of 1:2 for 20 h. The rotation mode is alternating forward and reverse (one cycle of 5 h) and the speed is 200 r / min. The powder particle size after ball milling is 0.5~5 μm.
[0062] Step 4: The ball-milled composite powder is kept at 80° C. in a forced air drying oven for 10 h, and then sieved with a 200-mesh sieve to ensure that the powder particles are fine and evenly dispersed.
[0063] Step 5: Prepare the WC-CuFeNiCrCo metal ceramic block by spark plasma sintering technology, wherein the sintering pressure is 40 MPa, the sintering temperature is 1100° C., and the holding time is 10 min.
[0064] Figure 5 The friction and wear performance test results of the WC-CuFeNiCrCo metal ceramic blocks prepared in Examples 1 to 3 are shown in Figure 1. The sample numbers corresponding to Examples 1 to 3 are WC-HEA-1, WC-HEA-2 and WC-HEA-3, respectively. As can be seen from the figure, the wear rates of the three groups of metal ceramic blocks are more than 4 times lower than that of the control sample (316L stainless steel), showing better wear resistance. In particular, the wear rate of the sample in Example 1 is relatively the lowest, which is only 0.96×10 -6 mm 3 / Nm.
[0065] Furthermore, the corrosion resistance of the WC-CuFeNiCrCo metal ceramic block prepared in Example 3 was tested by a neutral salt spray corrosion test, and the test conditions included: 5.0% NaCl solution, corrosion for 720 h, 5 parallel samples, and each sample was sealed before the test. After the test, the corrosion resistance of the sample was rated according to the GBT 6461-2002 standard. Figure 6 : is the neutral salt spray corrosion performance test result of each sample. It can be seen from the figure that after 720 h of corrosion, the corrosion level of the metal ceramic block prepared in Example 3 is stabilized at level 9, showing excellent corrosion resistance.
[0066] Example 4 This example is used to prepare a WC-10wt%CuFeNiCrCo metal ceramic block, and the specific implementation steps are as follows: Step 1: Prepare CuFeNiCrCo high entropy alloy powder using vacuum air atomization powder making equipment. The process parameters for preparing CuFeNiCrCo high entropy alloy powder include: air pressure of 10 MPa, air flow velocity of 200 mm / s, and air flow injection angle controlled at 45°. The particle size of the prepared CuFeNiCrCo high entropy alloy powder is 0.1~15 μm.
[0067] Step 2: weigh and mix the metal-ceramic composite powder, where the metal-ceramic composite powder may be a WC-CuFeNiCrCo composite powder. Without adding a grain inhibitor and an antioxidant, the metal-ceramic composite powder includes 10 wt% of CuFeNiCrCo high entropy alloy powder and 90 wt% of WC powder.
[0068] Step 3: The metal-ceramic composite powder and deionized water are ball-milled in a ratio of 1:2 for 20 h. The rotation mode is alternating forward and reverse (one cycle of 5 h) and the speed is 200 r / min. The powder particle size after ball milling is 0.5~5 μm.
[0069] Step 4: The ball-milled metal-ceramic composite powder is kept at 80° C. in a forced air drying oven for 10 h, and then sieved with a 200-mesh sieve to ensure that the powder particles are fine and evenly dispersed.
[0070] Step 5: Prepare the WC-CuFeNiCrCo metal ceramic block by spark plasma sintering, wherein the sintering pressure is 40 MPa, the sintering temperature is 1100° C., and the holding time is 10 min.
[0071] Compared with Example 3, Example 4 did not add a grain inhibitor and an antioxidant during the ball milling process. The deposited coatings of Example 3 and Example 4 were subjected to a neutral salt spray corrosion performance test, and the test conditions included: 5.0% NaCl solution, corrosion for 720 hours, 5 parallel samples, and each sample was sealed before the test; after the test, the corrosion resistance of the samples was rated according to the GBT 6461-2002 standard. Figure 6 The neutral salt spray corrosion test results of each sample are shown in FIG. 1 . It can be seen from the figure that after 720 h of corrosion, the corrosion grade of the coating in Example 3 (grade 9) is significantly higher than that of the coating in Example 4 (grade 7), indicating that the addition of grain inhibitors and antioxidants is beneficial to improving the corrosion resistance of the coating.
[0072] Example 5 This example is used to prepare WC-40wt%Cu 0.5 FeNiCr metal ceramic block, the specific implementation steps are as follows: Step 1: Prepare Cu using vacuum gas atomization powder making equipment 0.5 FeNiCr high entropy alloy powder. Preparation of Cu 0.5 The process parameters of FeNiCr high entropy alloy powder include: air pressure of 5 MPa, air flow velocity of 200 mm / s, and air flow injection angle of 60°. 0.5 The particle size of FeNiCr high entropy alloy powder is 0.1~15 μm.
[0073] Step 2: weigh and proportion the metal-ceramic composite powder, which may be WC-Cu 0.5 FeNiCr composite powder, metal ceramic composite powder including 10 wt% Cu 0.5 FeNiCr high entropy alloy powder, 90 wt% WC powder, 0.6 wt% grain inhibitor (complex phase carbide) and 0.6 wt% antioxidant.
[0074] Step 3: The metal-ceramic composite powder and deionized water are ball-milled in a ratio of 1:2. The ball-milling time is 30 h, the rotation mode is alternating forward and reverse (one cycle is 5 h), the speed is 300 r / min, and the powder particle size after ball-milling is 0.5~5 μm.
[0075] Step 4: The ball-milled metal-ceramic composite powder is kept at 80°C in a blast drying oven for 10 h, and then sieved with a 200-mesh screen to ensure that the powder particles are fine and evenly dispersed. Step 5: Prepare WC-Cu by spark plasma sintering 0.5 FeNiCr metal ceramic block, wherein the sintering pressure is 30 MPa, the sintering temperature is 1200 ℃, and the holding time is 10 min.
[0076] Example 6 This example is used to prepare WC-20wt%Cr3C2-10wt%Cu 0.2 FeNiCrAl metal ceramic composite powder and metal ceramic block, the specific implementation steps are as follows: Step 1: Prepare Cu using vacuum gas atomization powder making equipment 0.2 FeNiCrAl high entropy alloy powder. Preparation of Cu 0.2 The process parameters of FeNiCrAl high entropy alloy powder include: air pressure of 5 MPa, air flow velocity of 150 mm / s, and air flow injection angle of 30°. 0.2 The particle size of FeNiCrAl high entropy alloy powder is 0.1~15μm.
[0077] Step 2: Weigh and proportion WC-Cr3C2-Cu 0.2FeNiCrAl metal ceramic composite powder, in the case of adding grain inhibitor and antioxidant, the metal ceramic composite powder includes 10 wt% Cu 0.2 FeNiCrAl high entropy alloy powder, 70 wt% WC powder, 20 wt% Cr3C2 powder, 0.6 wt% grain inhibitor (complex phase carbide) and 0.6 wt% antioxidant.
[0078] Step 3: ball-mill the mixed metal-ceramic composite powder and deionized water in a ratio of 1:2 for 30 h, with a rotation mode of alternating forward and reverse rotation (5 h per cycle) and a rotation speed of 300 r / min. The particle size of the metal-ceramic composite powder after ball milling is 0.5~5 μm.
[0079] Step 4: Keep the ball-milled metal-ceramic composite powder at 80°C in a blast drying oven for 10 h, and then sieve it with a 300-mesh screen to ensure that the powder particles are fine and evenly dispersed. Step 5: Use hot isostatic pressing technology to sinter WC-Cr3C2-Cu 0.2 FeNiCrAl metal ceramic blocks were prepared with a sintering pressure of 30 MPa, a sintering temperature of 1200°C and a holding time of 60 min.
[0080] Example 7 The process is the same as that of Example 1, except that the composition of the prepared metal ceramic block is WC-10wt%Cr3C2-40wt%Cu 0.5 FeNiCrAl, the metal ceramic block is prepared by hot isostatic pressing sintering technology, wherein the sintering pressure is 20 MPa, the sintering temperature is 1300℃, and the holding time is 90 min.
[0081] Example 8 The process is the same as that of Example 1, except that the composition of the prepared metal ceramic block is WC-20wt%Cr3C2-10wt%CuFeNiCr 0.2 Ti, the metal ceramic block was prepared by hot pressing sintering technology, where the sintering pressure was 25 MPa, the sintering temperature was 1000 ℃, and the holding time was 120 min.
[0082] Example 9 The process is the same as that of Example 1, except that the composition of the prepared metal ceramic block is WC-10wt%Cr3C2-40wt%Cu 0.2 FeNiCr 0.5Ti, the metal ceramic block was prepared by hot pressing sintering technology, where the sintering pressure was 25 MPa, the sintering temperature was 1000 ℃, and the holding time was 120 min.
[0083] Example 10 The process is the same as that of Example 1, except that the composition of the prepared metal ceramic block is WC-20wt%B4C-20wt%CuFeNiCrCo, and the ball milling parameters of the metal ceramic composite powder include: ball milling time of 20 h, rotation mode of alternating forward and reverse rotation (2 h per cycle), rotation speed of 200 r / min, and powder particle size after ball milling is 0.5~5 μm.
[0084] Embodiment 11 The process is the same as that of Example 1, except that the composition of the prepared metal ceramic block is WC-40wt%Cu 0.5 FeNiCr 0.5 Ti, the metal ceramic block was prepared by hot pressing sintering technology, wherein the sintering pressure was 40MPa, the sintering temperature was 900℃, and the holding time was 30min.
[0085] Example 12 The process is the same as that of Example 1, except that the composition of the metal ceramic block used to prepare is WC-20wt% Cu 0.5 FeNiCrAl, the metal ceramic block is prepared by spark plasma sintering technology, wherein the sintering pressure is 40 MPa, the sintering temperature is 1100℃, and the holding time is 10 min.
[0086] Embodiment 13 The process is the same as that of Example 1, except that the composition of the metal ceramic block used to prepare is WC-20wt% Cu 0.2 FeNiCr 0.5 Al, the metal ceramic block was prepared by spark plasma sintering technology, where the sintering pressure was 25 MPa, the sintering temperature was 1000℃, and the holding time was 8 min.
[0087] Embodiment 14 The process is the same as that of Example 1, except that the composition of the metal ceramic block used to prepare is WC-10wt%Cr3C2-20wt%Cu 0.5 FeNiCr 0.5Co; ball milling time was 30 h, the rotation mode was alternating forward and reverse rotation (2 h for one cycle), and the speed was 250 r / min; hot pressing technology was used to prepare the metal ceramic block, where the sintering pressure was 25 MPa, the sintering temperature was 1200 ℃, and the holding time was 90 min.
[0088] Embodiment 15 The process is the same as that of Example 1, except that the composition of the metal ceramic block used to prepare is WC-10wt%B4C-20wt%Cu 0.5 FeNiCr 0.5 Co; ball milling time was 20 h, the rotation mode was alternating forward and reverse rotation (5 h for one cycle), and the speed was 250 r / min; hot isostatic pressing technology was used to prepare the metal ceramic block, where the sintering pressure was 30 MPa, the sintering temperature was 900 ℃, and the holding time was 120 min.
[0089] Comparative Example The selected material is ZrC-45wt%AlSiCrFeCoNi metal ceramic block, and the specific implementation steps are as follows: Step 1: Prepare AlSiCrFeCoNi alloy powder using vacuum air atomization powder making equipment. The process parameters for preparing AlSiCrFeCoNi alloy powder include: air pressure of 10 MPa, air flow velocity of 200 mm / s, and air flow injection angle controlled at 45°. The particle size of the prepared AlSiCrFeCoNi alloy powder is 0.1~10 μm.
[0090] Step 2: weigh and mix ZrC-AlSiCrFeCoNi composite powder, wherein the composite powder comprises 45 wt% of AlSiCrFeCoNi alloy powder and 55 wt% of ZrC powder.
[0091] Step 3: The mixed composite powder and deionized water were ball-milled in a ratio of 1:2. The ball-milling time was 20 h. The rotation mode was alternating forward and reverse rotation (one cycle was 5 h). The speed was 200 r / min. The powder particle size after ball milling was 0.5~5 μm.
[0092] Step 4: The ball-milled composite powder is kept in a forced air drying oven at 80°C for 10 h, and then sieved with a 200-mesh sieve to ensure that the powder particles are fine and evenly dispersed.
[0093] Step 5: Prepare ZrC-AlSiCrFeCoNi metal ceramic block by vacuum sintering process. The specific steps of preparing ZrC-AlSiCrFeCoNi metal ceramic block by vacuum sintering process include: First, the treated powder was poured into a φ50 mm mold and pressed into a body by a press at a pressure of 200 MPa. Then, the pressed carbide body was placed in a high-temperature furnace and heated under high vacuum conditions. The main parameters included: vacuum degree 10 -2 Pa, temperature 1100℃, holding time 60 min, heating rate 4℃ / min; finally, after the holding is completed, the furnace is cooled to room temperature to obtain a ZrC-AlSiCrFeCoNi metal ceramic block.
[0094] Figure 7 The test results of coating hardness and flexural strength of the metal ceramic block prepared in Example 3 and the comparative example are shown. The results show that the hardness of Example 3 reaches 94.5±0.9 HRA and the flexural strength is 1296±20 MPa, which are significantly higher than the hardness and flexural strength of the comparative example coating (90.3±0.7 HRA and 1132±35 MPa). The metal ceramic block prepared in the embodiment of the present disclosure exhibits better comprehensive mechanical properties.
[0095] In summary, in the embodiments of the present disclosure, MC-Cu is prepared based on the unique characteristics of high entropy alloys such as resistance to radiation damage, high oxidation resistance and good wettability. z FeNiCr y X new metal-ceramic composite powder. Using high entropy alloy as the metal phase can reduce the proportion of active elements in the coating and greatly improve the material's resistance to radiation damage. Taking into full consideration the high wettability, high toughness, corrosion resistance and radiation damage resistance of the composite material's bonding phase, four elements with similar atomic radius, Fe, Ni, Cr and Cu, are selected as the basic elements of high entropy alloy powder to form a high entropy alloy with FCC structure. Among them, Fe, Ni and Cr can increase the chaotic entropy of the alloy and promote the formation of high entropy alloy; the addition of Cr is also conducive to the formation of Cr2O3 and improves the corrosion resistance of the alloy; the addition of Cu can improve the wettability of high entropy alloy and carbide hard phase, improve the density and cohesive strength of the composite material; doping with elements such as Co, Al and Ti can adjust the degree of lattice distortion of the FCC phase of the high entropy alloy, change the mechanical properties of the alloy, and realize the functional diversification of the composite material.
[0096] Further, in the disclosed embodiment, the WC particles as MC carbides and the high entropy alloy phase are uniformly distributed by long-term aging, positive-reverse alternation and wet ball milling, which not only effectively solves the problem of WC particle segregation in the process of mixing WC-based powder by traditional ball milling, but also avoids the problem of high entropy alloy phase sticking at high temperature, ensuring the stability of each phase content in the composite powder. In addition, a grain inhibitor is used to inhibit the growth of carbide grains during high-temperature sintering. By adding a grain inhibitor formed by a mixture of two multiphase carbides during the ball milling process, the excessive growth of nano-scale and submicron-scale carbide particles during the sintering process can be simultaneously inhibited, effectively improving the mechanical properties of the composite material. When ball milling and mixing, an antioxidant is added to the composite powder to eliminate the oxide impurities generated during the ball milling of the composite powder, which helps to improve the density of the sintered block, and can inhibit the crack initiation and expansion behavior under high external stress, and improve the overall fracture toughness of the material. In addition, by inhibiting the crack expansion behavior, the number of corrosion channels can be reduced, further improving the corrosion resistance of the material.
[0097] High-performance MC-Cu is achieved through powder hot forming technologies such as hot pressing, hot isostatic pressing and spark plasma sintering. z FeNiCr y Stable preparation of X metal ceramic blocks. Under the process parameters in the disclosed embodiments, the high entropy alloy binder phase can be fully melted into a liquid phase to coat WC particles of different particle sizes and tightly bond the hard particles, effectively improving the density and mechanical properties of the composite material. In addition, the appropriate sintering pressure and temperature ratio can avoid the overflow and loss of liquid high entropy alloy along the gap between the hot pressing mold and the sample, effectively ensuring the stability of the sample structure and performance.
[0098] The technical solution in the disclosed embodiment combines the high corrosion resistance of carbides and the high radiation damage resistance of high entropy alloys, and is supported by powder mixing technology and hot pressing technology with the characteristics of long aging, positive-reverse alternation and wet ball milling. z FeNiCr y X high entropy alloy replaces Co binder phase, and a corrosion-resistant high entropy metal ceramic composite material is designed and prepared. Compared with traditional metal ceramics, high entropy metal ceramics have better corrosion resistance and can significantly improve the service life and stability of reactors.
[0099] In the embodiments of the present disclosure, a high entropy metal ceramic material is also provided. The high entropy metal ceramic material can be prepared according to the method of step S110 to step S120.
[0100] In the embodiment of the present disclosure, in order to meet the coupled harsh working conditions of lead-cooled fast reactor corrosion, wear and radiation damage, hard carbide with high corrosion resistance is combined with high entropy alloy with excellent radiation damage resistance to prepare MC-Co by vacuum atomization method and mechanical ball milling method. z AlFeNiCrX metal ceramic composite powder, and successfully prepared MC-Co by powder hot forming technology z AlFeNiCrX metal ceramic block. Prepared MC-Cu z FeNiCr y The X-metal ceramic block has a dense structure and a hardness of more than 90 HRA. After sealing, it was subjected to 720 h of neutral salt spray corrosion, and the corrosion level reached level 9. Compared with traditional metal ceramics, high-entropy metal ceramics have better corrosion resistance and can significantly improve the service life and stability of the reactor and improve its quality.
[0101] In addition, the above-mentioned figures are only schematic illustrations of the processes included in the method according to the exemplary embodiments of the present disclosure, and are not intended to be limiting. It is easy to understand that the processes shown in the above-mentioned figures do not indicate or limit the time sequence of these processes. In addition, it is also easy to understand that these processes can be performed synchronously or asynchronously, for example, in multiple modules.
[0102] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
[0103] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing a high entropy metal ceramic material, characterized in that: include: Preparation of Cu z FeNiCr y X high entropy alloy powder, based on Cu z FeNiCr y X high entropy alloy powder and MC carbide are used to prepare metal-ceramic composite powder, and the metal-ceramic composite powder is ball-milled to obtain MC-Cu with dispersed carbide particles. z FeNiCr y X metal ceramic powder; MC-Cu is formed by powder hot forming technology z FeNiCr y X metal ceramic powder is prepared into a metal ceramic block to obtain a high entropy metal ceramic material.
2. The method for preparing a high entropy metal ceramic material according to claim 1, characterized in that: The Cu z FeNiCr y X high entropy alloy powder is prepared by vacuum atomization method and is used to prepare Cu z FeNiCr y The process parameters of X high entropy alloy powder include: air pressure 1~10 MPa, air flow velocity 100~200 mm / s, and air flow injection angle 30~90°.
3. The method for preparing a high entropy metal ceramic material according to claim 1, characterized in that: The Cu z FeNiCr y X in the X high entropy alloy powder includes any one of Co, Al and Ti; Cu z FeNiCr y The range of z and y in X high entropy alloy powder is 0~1.0 at%, Cu z FeNiCr y The particle size of X high entropy alloy powder is 0.1~15 μm.
4. The method for preparing a high entropy metal ceramic material according to claim 1, characterized in that: The MC carbide is WC, WC-Cr3C2 or WC-B4C, and the particle size of the MC carbide is 1-3 μm.
5. The method for preparing a high entropy metal ceramic material according to claim 1, characterized in that: The MC-Cu z FeNiCr y X cermet powder contains 5~40 wt% Cu z FeNiCr y X high entropy alloy powder and 60~95 wt% MC carbide.
6. The method for preparing a high entropy metal ceramic material according to claim 1, characterized in that: During the ball milling process, 0.1-1.0 wt% of a grain inhibitor and 0.1-1.0 wt% of an antioxidant are added, wherein the grain inhibitor comprises chromium carbide and vanadium carbide.
7. The method for preparing a high entropy metal ceramic material according to claim 1, characterized in that: The ball milling time is 20-40 h, the ball milling rotation mode is in a cycle of positive-reverse alternation, the ball milling speed is 100-300 r / min, and the MC-Cu obtained after ball milling z FeNiCr y The particle size of X metal ceramic powder is 0.5~5 μm.
8. The method for preparing a high entropy metal ceramic material according to claim 1, characterized in that: The MC-Cu z FeNiCr y X metal ceramic powder is prepared into a metal ceramic block, including: MC-Cu z FeNiCr y X metal ceramic powder is dried and kept warm, and MC-Cu is formed by powder hot forming technology. z FeNiCr y The X metal ceramic powder is sintered to prepare the high entropy metal ceramic material.
9. The method for preparing a high entropy metal ceramic material according to claim 8, characterized in that: The sintering pressure is 10-40 MPa, the sintering temperature is 900-1400° C., and the insulation time is 5-120 min.
10. A high entropy metal ceramic material, characterized in that: The high entropy metal ceramic material is prepared according to the preparation method of the high entropy metal ceramic material according to any one of claims 1-9.
Citation Information
Patent Citations
Titanium carbonitride based metal ceramic based on high-entropy alloy binder phase and preparation method of metal ceramic
CN102787266A
High-entropy alloy binding phase ultrafine tungsten carbide hard alloy and preparation method thereof
CN109252081A
KR20240062321A